2022
DOI: 10.18596/jotcsa.1003132
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methylene Blue and Methyl Orange from Aqueous Solution using Orange Peel and CTAB-Modified Orange Peel

Abstract: Cationic and anionic dyes are frequently used in industrial sectors and cause many environmental and health problems. Orange peel has the potential to absorb dye as an adsorbent. This study aimed to explore the adsorption of methylene blue (MB) as a cationic dye and methyl orange (MO) as an anionic dye using orange peel (OP) and its modification using cetyltrimethylammonium bromide (CTAB). OP and OP-CTAB biomass materials were characterized using FT-IR (Fourier transform infrared), surface area analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
(14 reference statements)
0
2
1
Order By: Relevance
“…The net negative charge (CEC) and the specific surface area explain the order of adsorption of Pb (II) and Cr (III) on the peels, since the CEC and the specific surface area (Table 2) were greatest in PF, followed by OP then by PP. The specific surface area of OP, PP, and PF increased with decreasing particle size (Table 2), but the values in this study were lower than those found by Amel et al [47], Dey et al [48], Feng and Guo [34], Kamsonlian et al [49], Rosanti et al [50], Salman and Ali [51] for orange peel (0.452-204 m 2 g À1 ), El-Azazy et al [52] for potato rind (4.075 m 2 g À1 ), and Chen et al [53] for passion fruit peel (4.403 m 2 g À1 ).…”
Section: Removal Of Lead and Chromium From The Aqueous Solutioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The net negative charge (CEC) and the specific surface area explain the order of adsorption of Pb (II) and Cr (III) on the peels, since the CEC and the specific surface area (Table 2) were greatest in PF, followed by OP then by PP. The specific surface area of OP, PP, and PF increased with decreasing particle size (Table 2), but the values in this study were lower than those found by Amel et al [47], Dey et al [48], Feng and Guo [34], Kamsonlian et al [49], Rosanti et al [50], Salman and Ali [51] for orange peel (0.452-204 m 2 g À1 ), El-Azazy et al [52] for potato rind (4.075 m 2 g À1 ), and Chen et al [53] for passion fruit peel (4.403 m 2 g À1 ).…”
Section: Removal Of Lead and Chromium From The Aqueous Solutioncontrasting
confidence: 77%
“…[ 49 ], Rosanti et al. [ 50 ], Salman and Ali [ 51 ] for orange peel (0.452–204 m 2 g −1 ), El-Azazy et al. [ 52 ] for potato rind (4.075 m 2 g −1 ), and Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, many adsorbents have been reported for the removal of methyl orange such as chitosan derivatives [ 1 , 17 , 18 ], agriculture waste [ 2 , 19 , 20 , 21 ], biochar [ 3 , 22 ], clay [ 23 ], activated carbon, mesoporous silica, alumina [ 24 ], carbon nanotubes [ 25 ], nanocomposites [ 10 , 12 ], polymers, and many others [ 4 ]. Despite all the progress in this area of research, many challenges still face the application of adsorption at commercial levels due to one or more of the following adsorbent drawbacks: a low adsorption capacity, slow rate of adsorption, biodegradation of the adsorbent, low stability, high cost, complex synthesis procedure, and low selectivity and sensitivity at low concentration levels.…”
Section: Introductionmentioning
confidence: 99%